1998
DOI: 10.1038/sj.bmt.1701163
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring soluble interleukin-2 receptor levels in related and unrelated donor allogeneic bone marrow transplantation

Abstract: Summary:Acute graft-versus-host disease (GVHD) is effected by donor T lymphocytes which have been stimulated by host antigens. Activated donor T lymphocytes express interleukin-2 receptor (IL-2R), which is comprised of three subunits (␣, ␤, ␥). During activation, the ␣ IL-2R subunit (CD25) is shed from the receptor complex and can be measured in the circulation. Soluble IL-2R␣ (sIL-2R) levels are increased in states of immune activation including GVHD, and could theoretically be used as a guide to therapy. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
2
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 14 publications
1
39
2
6
Order By: Relevance
“…Serum levels of soluble IL-2R (sIL-2R), although increased post UCBT within the first week, were not higher in patients with more severe aGVHD grade II-IV as compared to patients with grade 0-I aGVHD, and could not predict early onset of severe aGVHD. This finding was in contrast to what was reported by other investigators, 8,[35][36][37] who found a significant elevation of sIL-2R as early as 3 days 8 or up to 2 weeks 36 post allogeneic BMT in patients with aGVHD that correlated with the severity of aGVHD and returned to normal levels when aGVHD was clinically controlled.…”
Section: Discussioncontrasting
confidence: 56%
“…Serum levels of soluble IL-2R (sIL-2R), although increased post UCBT within the first week, were not higher in patients with more severe aGVHD grade II-IV as compared to patients with grade 0-I aGVHD, and could not predict early onset of severe aGVHD. This finding was in contrast to what was reported by other investigators, 8,[35][36][37] who found a significant elevation of sIL-2R as early as 3 days 8 or up to 2 weeks 36 post allogeneic BMT in patients with aGVHD that correlated with the severity of aGVHD and returned to normal levels when aGVHD was clinically controlled.…”
Section: Discussioncontrasting
confidence: 56%
“…Whether the sIL-2R level after HSCT is a good indicator of aGVHD remains unclear. 11,12,29 In the present study, there was a tendency to significance between a high sIL-2R level and the severity of aGVHD, but statistical significance was not established because the plasma sIL-2R level was increased in the patients with an infection. TNF-␣ and IFN-␥ were thought to be an effector cytokine for the development of GVHD, but no definite peak of either cytokine could be found in plasma samples obtained after HSCT in our study.…”
Section: Comparison Of Post-hsct Cytokines and Soluble Receptors Levementioning
confidence: 68%
“…7,10 Elevation of serum soluble IL-2 receptor (sIL-2R) has been found in GVHD, veno-occlusive disease and infection. 11,12 IL-6 is also involved in the development of GVHD and infections following bone marrow transplantation (BMT). [13][14][15] Furthermore, tumor necrosis factor (TNF)-␣, interferon (IFN)-␥ and IL-15 were reported to be involved in the development of GVHD.…”
mentioning
confidence: 99%
“…16 However, numerous candidate GVHD biomarkers have been studied during the past years, almost all of them belonging to the cytokine cascades driving GVHD effector cells, such as gammainterferon and the soluble form of its receptor, sTNF-R, interleukin 6 (IL-6), IL-8, IL-18, ICAM-1, IL-1, IL-10, IL-12, IL-2, IL-4, and-investigated best-soluble interleukin-2 receptor (sIL2-R, sCD25). [17][18][19][20][21][22][23][24] Although in particular sCD25 and IL-18 showed some association with (acute) GVHD, lack of specificity 18,19,25 and poor correlation to GVHD intensity 26 have precluded their routine use for GVHD monitoring either alone or in the context of multifactorial grading systems.…”
Section: Discussionmentioning
confidence: 99%